Experimental investigation on the use of highly charged nanoparticles to improve the stability of weakly charged colloidal system - Zubir, M.N.M.; Badarudin, A.; Kazi, S.N.; Misran, M.; Amiri, A.; Sadri, R.; Khalid, S. (Elsevier, 2015)
The present work highlighted on the implementation of a unique concept for stabilizing colloids at their incipiently low charge potential. A highly charged nanoparticle was introduced within a coagulated prone colloidal system, serving as stabilizer to resist otherwise rapid flocculation and sedimentation process. A low size asymmetry of nanoparticle/colloid serves as the new topic of investigation in addition to the well-established large size ratio nanoparticle/microparticle study. Highly charged Al2O3 nanoparticles were used within the present research context to stabilize TiO2 and Fe3O4 based colloids via the formation of composite structures. It was believed, based on the experimental evidence, that Al2O3 nanoparticle interact with the weakly charged TiO2 and Fe3O4 colloids within the binary system via absorption and/or haloing modes to increase the overall charge potential of the respective colloids, thus preventing further surface contact via van der Waal's attraction. Series of experimental results strongly suggest the presence of weakly charged colloids in the studied bimodal system where, in the absence of highly charged nanoparticle, experience rapid instability. Absorbance measurement indicated that the colloidal stability drops in accordance to the highly charged nanoparticle sedimentation rate, suggesting the dominant influence of nanoparticles to attain a well-dispersed binary system. Further, it was found that the level of colloidal stability was enhanced with increasing nanoparticle fraction within the mixture. Rheological observation revealed that each hybrid complexes demonstrated behavior reminiscence to water with negligible increase in viscosity which serves as highly favorable condition particularly in thermal transport applications. (C) 2015 Elsevier Inc. All rights reserved.